BANK INDONESIA’S ROLE IN ERADICATING CORRUPTION: ADOPTING THE WORLD BANK INITIATIVES - Natamiharja, Rudi; Sabatira, Febryani; Davey, Orima Melati; Khanza, Yuga Narazua (Bank Indonesia, 2024)
Bank Indonesia as the primary agent for maintaining state financial stability plays an essential role in combatting corruption through preventive and repressive measures. However, considering the poor state of corruption management, Indonesia requires a more strategic and measurable framework. In this case, The World Bank Group (WBG) has numerous methods for combatting corruption through structured initiatives. The overall goal of the programs is to achieve a high level of transparency as the central bank’s fundamental premise in dealing with corruption. Thus, by adopting the WBG guidelines and initiatives, Indonesia can gradually scale up its corruption eradication efforts. This study will further highlight three areas, namely: (i) the World Bank alternatives for controlling corruption; (ii) the role of Bank Indonesia in eradicating corruption; and (iii) adoption of the World Bank’s alternatives in strengthening Bank Indonesia’s efforts to eradicate corruption. The study uses normative legal research using a regulatory approach with secondary data collection. The results of the study show that Bank Indonesia has thoroughly adopted the World Bank’s initiatives. Nevertheless, BI still needs to optimise technology-based public transparency, enhance public involvement, and strengthen supervision of sectoral-based corruption risk in the future.